2012
DOI: 10.1016/j.acvd.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of blood pressure reflects the severity of cardiac impairment in familial amyloid polyneuropathy

Abstract: Low blood pressure variability is common in cardiac amyloidosis due to FAP. A non-dipping pattern was more frequently observed in FAP patients with haemodynamic impairment, cardiac thickening or conduction disorders. It is suggested that impairment of circadian rhythm of blood pressure reflects the severity of cardiac amyloidosis due to FAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Rhythm disturbances and conduction defects are frequent consequences of cardiac amyloidal infiltration. Such as other studies, 14,26 we observed an increase in their occurrence with the worsening of TTR-FAP. It has been suggested that conduction defects can be relatively dissociated from LV thickening 14 and may even worsen after liver transplantation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Rhythm disturbances and conduction defects are frequent consequences of cardiac amyloidal infiltration. Such as other studies, 14,26 we observed an increase in their occurrence with the worsening of TTR-FAP. It has been suggested that conduction defects can be relatively dissociated from LV thickening 14 and may even worsen after liver transplantation.…”
Section: Discussionsupporting
confidence: 60%
“…As in other studies, abnormalities in circadian BP variation were frequently detected. 26,27 High BP and the decrease in nocturnal systolic BP drop were the most common cardiovascular abnormalities and were more pronounced in patients with neurological involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambulatory BP monitoring (ABPM) can help in the diagnosis and management of nOH [99]. Affected patients typically have a reversal of the normal circadian blood pressure pattern with higher BP during the night when the patient is supine in bed than during the day (i.e., non-dipping BP) [5, 22]. Nocturnal supine hypertension causes pressure natriuresis with exaggerated sodium and water loss causing overnight depletion of intravascular volume, worsening OH in the morning.…”
Section: Diagnosis Of Neurogenic Ohmentioning
confidence: 99%
“…Mean late HMR in patients without neuropathy 2.2 ± 0.5 vs patients with neuropathy 1.5 ± 0.4 ( P = 0.001) N/A 9 Delahaye et al 11 31 patients 300 MBq (8 mCi) [I-123]-MIBG LE 4 hours p.i. hATTR Mean late HMR 2 years after liver transplantation 1.46 ± 0.28 vs 6 months before liver transplantation 1.45 ± 0.29, P = not significant No cardiac death or lethal arrhythmia reported 10 Algalarrando et al 36 32 patients 300 MBq (8 mCi) [I-123]-MIBG LE 4 hours p.i. hATTR Late HMR ≤1.6 in 26 out of 32 patients No cardiac death or lethal arrhythmia reported 11 Noordzij et al 12 61 patients, 9 healthy control subjects 185 MBq (5 mCi) [I-123]-MIBG ME 4 hours p.i.…”
Section: Imaging Of Cardiac Innervation In Amyloidosismentioning
confidence: 99%